Digital infrared thermal imaging of human skin. - Jones, B.F.
Describes computational approaches to image processing for improved interpretation and analysis. The authors discuss the physics of image formation, developments in uncooled camera technology, and the use of image processing to interpret 2-D maps of temperatures and to analyze thermal images for assessing physiological changes and responses to physical provocations and stresses such as brief exposure to low temperatures.
Keywords: Brief exposure to low temperatures; Digital infrared thermal imaging; Human skin; Image formation physics; Improved interpretation; Medical diagnostic imaging; Physiological changes assessment; Responses to physical provocations; Uncooled camera technology developments